Augmented Renal Clearance. Issue 3 (11th March 2019) - Cook, Aaron M.; Hatton‐Kolpek, Jimmi
Abstract : Augmented renal clearance (ARC) is a phenomenon in critically ill patients characterized by increased creatinine clearance and elimination of renally eliminated medications. Patients with severe neurologic injury, sepsis, trauma, and burns have been consistently identified as at risk of ARC, with mean creatinine clearances ranging from 170 ml/minute to more than 300 ml/minute. Several potential mechanisms may contribute to the occurrence of ARC including endogenous responses to increased metabolism and solute production, alterations in neurohormonal balance, and therapeutic maneuvers such as fluid resuscitation. Augmented renal clearance is associated with suboptimal exposure to critical medications, including β‐lactams and vancomycin, increasing the risk of treatment failure. Although definitive screening tools are not yet known, critical care pharmacists must be vigilant in recognizing when ARC may be a contributing factor affecting expected treatment outcomes in individual patients. Optimizing dosing strategies in critically ill patients with ARC remains a goal of continued research. The current review discusses the clinical characteristics and methods of identifying patients at risk of ARC, potential mechanisms for ARC, and describes pharmacotherapy dosing considerations in patients with ARC.